Mareks Disease in An Aseel Chicken - Cytohistopathological Approach - Kumar, V.; Pazhanivel, N.; Gopal, K.; Thangathurai, R.; Balachandran, C. (Indian Journal of Veterinary Sciences and Biotechnology, 2017)
Mareks diseases (MD) is a lymphoproliferative disease of chicken affecting all organs including skin. Mareks disease is become a menace to the poultry industry owing to the serious economic loss. MD is caused by herpes virus with three serotype of MDV (Carter et al., 2006). MD is a very serious problem and it produces up to 60% of mortality in layers and 10% of mortality in broilers. Epidemiological data recorded average about 10–40% flock mortality (Arulmozi et al. 2011). The clinical feature of MD is characterized by paralysis of the wings, legs and neck with lameness, depression and death occurred. The present paper reports the occurrence of MD in Aseel chicken.